Crimean-Congo hemorrhagic fever virus in tortoises and Hyalomma aegyptium ticks in East Thrace, Turkey: potential of a cryptic transmission cycle - Kar, Sirri; Rodriguez, Sergio E.; Akyildiz, Gurkan; Cajimat, Maria N. B.; Bircan, Rifat; Mears, Megan C.; Bente, Dennis A.; Keles, Aysen G. (Parasites & vectors, 2020)
Background Recent reports have demonstrated the presence of Crimean-Congo hemorrhagic fever virus (CCHFV) genomic material in Hyalomma aegyptium ticks feeding primarily on tortoises belonging to the genus Testudo . This raises the question if these ticks and their hosts play a role in the natural transmission dynamics of CCHFV. However, the studies are limited, and assessing the relevance of H. aegyptium in perpetuating the virus in nature, and a potential spillover to humans remains unknown. This study aimed to detect CCHFV in H. aegyptium ticks and their tortoise hosts in the East Thrace region of Turkey, where H. aegyptium is the most common human-biting tick and where a high density of tortoises of the genus Testudo can be found. Methods During the study period, 21 blood samples from different tortoises (2 T. hermanni and 19 T. graeca ), 106 tick pools (containing 448 males, 152 females, 93 nymphs and 60 larvae) collected from 65 tortoises (5 T. hermanni and 60 T. graeca ), 38 adult unfed questing ticks (25 males and 13 females, screened individually) and 14 pools (containing 8 nymphs and 266 larvae) of immature unfed questing ticks collected from the ground were screened for CCHFV genome by nested PCR and partial genomes sequenced. Results As a result of the screening of these 179 samples, 17 (9.5%) were detected as positive as follows: 2 of 21 blood samples (9.52%), 13 (containing 18 nymphs in 3 pools, and 52 males and 8 females in 10 pools) of 106 tick pools from tortoises (12.26%), and 2 of 38 adult questing ticks (5.26%). No positive result was determined in 14 pools of immature questing ticks. Conclusions Previous studies have shown that reptiles can participate in the transmission of arthropod-borne viruses, but they may contribute to different aspects of the disease ecology and evolution of tick-borne viral pathogens. Our results indicate the presence of CCHFV in questing and feeding H. aegyptium ticks as well as tortoise hosts. This may indicate that CCHFV circulates in a cryptic transmission cycle in addition to the primary transmission cycle that could play a role in the natural dynamic of the virus and the transmission to humans.